Regional regulators in health care service under quality competition: A game theoretical model. (25th July 2018) - Bisceglia, Michele; Cellini, Roberto; Grilli, Luca
Abstract: In several countries, health care services are provided by public and/or private subjects, and they are reimbursed by the government, on the basis of regulated prices (in most countries, diagnosis‐related group). Providers take prices as given and compete on quality to attract patients. In some countries, regulated prices differ across regions. This paper focuses on the interdependence between regional regulators within a country: It studies how price setters of different regions interact, in a simple but realistic framework. Specifically, we model a circular city as divided in two administrative regions. Each region has two providers and one regulator, who sets the local price. Patients are mobile and make their choice on the basis of provider location and service quality. Interregional mobility occurs in the presence of asymmetries in providers' cost efficiency, regulated prices, and service quality. We show that the optimal regulated price is higher in the region with the more efficient providers; we also show that decentralisation of price regulation implies higher expenditure but higher patients' welfare.